Diagnosis and management of ADHD: a pediatric perspective on practice and challenges in Switzerland - A. Zysset; D. Robin; K. Albermann; J. Dratva; S. Hotz; F. Wieber; M. von Rhein (BMC, 2023)
Abstract Background Attention deficit/hyperactivity disorder (ADHD) is one of the most prevalent psychiatric disorders in childhood. In Switzerland, the complex diagnosis and treatment are being carried out by adolescent−/child psychiatrists, and pediatricians. Guidelines recommend a multimodal therapy for patients with ADHD. However, it has been questioned whether health professionals follow this approach or favor drug therapy. This study aims to provide insights into the practice of pediatricians in Switzerland regarding diagnosis and treatment of ADHD and their perceptions of these processes. Method An online survey (self-report) about current practices of diagnosis and management as well as challenges regarding ADHD was distributed to office-based pediatricians in Switzerland. One hundred fifty-one pediatricians participated. Results show that therapy options were almost always discussed with parents and older children. Exchange with parents (81%) and level of child's suffering (97%) were central when selecting therapy options. Results Therapies about which pediatricians informed most often were: pharmacological therapy, psychotherapy, and multimodal therapy. Challenges voiced were the subjectivity of diagnostic criteria and dependence on third parties, low availability of psychotherapy, and a rather negative public attitude towards ADHD. Needs that were expressed were further education for all professionals, support for coordination with specialists and schools as well as improvement of information on ADHD. Conclusions Pediatricians do consider a multimodal approach when treating ADHD and take the families` and children's opinions into account. Improvements of the availability of child and youth psychotherapy, the strengthening of the interprofessional cooperation with therapists and schools, and efforts to increase public knowledge about ADHD are proposed.